How to Manage The Liquidity and Fight The Firm Debt - Yanko Hristozov (International Business and Accounting Research Journal, 2018)
The liquidity is one of the most popular and used financial indicators for solvency at enterprises. The present study attempts to identify the key factors of managing the liquidity in enterprises, and the ability of influence by financial managers on them in order to provide "fresh" money. The problem with the liquidity provision has always stayed open for most economic subjects, especially during the financial and economic crises of the 21st Century.